Optimization of Bhabinkamtibmas Counseling Guidelines for the Prevention of Criminal Actions of Fraud in the Jurisdiction of The Police Areas of North Lampung - Alfredo Jaka Androla (Advances in Police Science Research Journal, 2021)
The research conducted by the author is motivated by the high number of cases of fraud in the jurisdiction of the North Lampung Police. This case has even increased over the last four years from 2017 to 2020. The preventive efforts that have been carried out have not been able to prevent or reduce these crimes. Therefore, a research was conducted to determine the efforts of counseling guidance and the methods used by Bhabinkamtibmas as a form of implementation of preventive efforts. The research was conducted using a qualitative approach, using field research research methods, as well as data collection techniques with interviews, observations, and document studies. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study showed that the counseling guidance activities carried out by the Bhabinkamtibmas of the North Lampung Police were still not optimal. This can be seen from the efforts and methods used are still not optimal in terms of the Chief of Police Regulation Number 21 of 2007. The existence of missed efforts and methods causes the counseling activities to be not optimal. Referring to the results of the study, the authors suggest that the leadership can re-evaluate the preventive efforts that have been carried out, provide opportunities for Bhabinkamtibmas to participate in training on the development of the Binmas function and hold regular training, form a forum to accommodate community aspirations and complaints, and Bhabinkamtibmas establish cooperation and relationships. with community agencies or organizations.